Dicranodromia danielae, a new species of homolodromiid crab from the Philippines (Crustacea: Decapoda: Brachyura) - Ng, Peter K.l.; Mclay, Colin L. (Zootaxa, 2005)
A new species of homolodromiid crab, Dicranodromia danielae n. sp., is reported from Balicasag Island, Panglao, Philippines. The new species is allied to D. doederleini Ortmann, 1892, This brings to two the number species known from the Philippines including D. martini Guinot, 1995, described from Cagayan and off Mindanao islands. Most species of Dicranodromia are found deeper than 400 m, but the new species was collected from 200 to 300 m.